2014
DOI: 10.3109/14767058.2014.913130
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of venous thromboembolism during pregnancy and the puerperium: a systematic review and meta-analysis

Abstract: Women during pregnancy or puerperium are associated with a higher morbidity of VTE. Physicians should be of high vigilance to pregnancy-associated VTE, especially for women postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 30 publications
3
65
1
10
Order By: Relevance
“…Based on several case‐controlled studies and meta‐analyses, the risk of venous thromboembolism during pregnancy and puerperium is greatly increased due to the maternal hypercoagulable states . However, no case‐controlled studies have confirmed the role of pregnancy and puerperium in the development of BCS.…”
Section: Pregnancy and Puerperiummentioning
confidence: 99%
See 1 more Smart Citation
“…Based on several case‐controlled studies and meta‐analyses, the risk of venous thromboembolism during pregnancy and puerperium is greatly increased due to the maternal hypercoagulable states . However, no case‐controlled studies have confirmed the role of pregnancy and puerperium in the development of BCS.…”
Section: Pregnancy and Puerperiummentioning
confidence: 99%
“…Based on several case-controlled studies and meta-analyses, the risk of venous thromboembolism during pregnancy and puerperium is greatly increased due to the maternal hypercoagulable states. [159][160][161][162] However, no case-controlled studies have confirmed the role of pregnancy and puerperium in the development of BCS. Ren et al systematically reviewed the relevant literature regarding the epidemiological profiles of pregnancyrelated BCS.…”
Section: Pregnancy and Puerperiummentioning
confidence: 99%
“…The risk of VTE that can manifest as deep vein thrombosis or pulmonary embolism was significantly higher among postpartum women than among pregnant women . A systematic review and meta‐analysis validated the higher morbidity of VTE in pregnant and postpartum women . In this perspective, several studies have suggested that SSNHL during the pregnancy or postpartum periods may be linked to vascular occlusion in the microcirculation due to blood coagulation and fibrinolysis .…”
Section: Discussionmentioning
confidence: 99%
“…25 A systematic review and metaanalysis validated the higher morbidity of VTE in pregnant and postpartum women. 26 In this perspective, several studies have suggested that SSNHL during the pregnancy or postpartum periods may be linked to vascular occlusion in the microcirculation due to blood coagulation and fibrinolysis. 9,27 However, evidence regarding thromboembolic occlusion in the cochlea that cause SSNHL has not yet been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of ambulation must be discussed with the patient and her family in the case of high-risk or Cesarean births given the increased risk of deep vein thrombosis with prolonged inactivity (Meng, Hu, Peng, & Zhang, 2015). Limited ambulation and avoidance of fi ber inherent in cold food (fruit, vegetables) also increases the risk of developing constipation.…”
Section: Mandated Restmentioning
confidence: 99%